2019
DOI: 10.3389/fpsyg.2019.01474
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Social Creativity in Science Education With Digital Technology to Overcome Inequalities: A Scoping Review

Abstract: Enhancing creativity and developing technology skills in the classroom are the future of education and can turn out to be powerful tools to smooth out inequalities in class. This paper presents a systematic scoping review study of the literature focusing on cases of social creativity and digital technology embedded in science education. To this end, 23 empirical studies were selected from several databases—all in English and subjected to a blind peer-review process—to address the interconnectedness of key them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 52 publications
0
14
0
1
Order By: Relevance
“…In our preliminary study, significant differences are shown in terms intelligence in favor of cognitive high-ability groups. Data show high abilities are linked to more possibilities of improving, perfecting or adding new elements to an initial idea [32]. This is the capacity of being creative and seems to be present in the high-ability students evaluated.…”
Section: Discussionmentioning
confidence: 89%
“…In our preliminary study, significant differences are shown in terms intelligence in favor of cognitive high-ability groups. Data show high abilities are linked to more possibilities of improving, perfecting or adding new elements to an initial idea [32]. This is the capacity of being creative and seems to be present in the high-ability students evaluated.…”
Section: Discussionmentioning
confidence: 89%
“…The contributions of this study in the teaching and learning process of high-ability students are clear [ 30 , 31 ], and they coincide with the contributions of the Gagne model. This model helps us to process the information and to understand the information being processed or transformed as structures are elaborated and reworked [ 32 ]. Therefore, the largest number of high-ability students should be identified to be able to offer the attention required to enhance their talent and abilities [ 17 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The business incubator centers in the United States and Poland are forms of social support for innovativeness and entrepreneurship (Al-Mubaraki et al, 2017;Malecki, 2018;Hassan, 2020;Wolniak et al, 2019;Hausberg and Korreck, 2020;Torun et al, 2018). Technical education and a large number of STEM (Science, Technology, Engineering, Mathematics) graduates are affected and linked to social support for innovativeness and entrepreneurship (Niittylahti et al, 2021;Saw, 2020;Aguilar and Turmo, 2019;Garcia-Morales et al, 2021;Haviland and Robbins, 2021;Grebski and Grebski, 2016;Grebski and Grebski, 2019;Aguilar and Turmo, 2019;Garcia-Morales et al, 2021;Haviland and Robbins, 2021). A social culture of respecting and protecting intellectual property is also a another form of social support for innovative behavior (Holgersson et al, 2018;Grebski and Wolniak, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%